Phytochemical Screening And Test For Reducing Uric Acid Levels In Male Rats After Administration Of Ethanol Extract Of The Herb Binara (Artemisia vulgaris L.) - Situmorang, Novidawati Boru; Harahap, Urip; Hasibuan, Poppy Anjelisa Z. (Publisher Cv. Inara, 2023)
Hyperuricemia is a metabolic disease generally characterized by high uric acid levels in the blood. The general treatment strategy for hyperuricemia is to decrease uric acid production using xanthine oxidation reductase inhibitors such as allopurinol and uricosuric agents. However, the drugs showed side effects, including skin rashes, diarrhoea and liver damage. To overcome the side effects of synthetic drugs, alternatives are used, namely by researching to find plants that have activity in reducing uric acid levels. The activity of reducing uric acid levels in plants is likely due to the presence of flavonoid compounds as antioxidants. Flavonoids active in reducing uric acid levels are kaempferol through xanthine oxidase inhibitors. Quercetin also has the potential to reduce uric acid levels through inhibition of the xanthine oxidase enzyme. Binara plant (Artemisia vulgaris L.) has flavonoids, tannins, alkaloids, glycosides and saponins which have potential as antioxidants and analgesics, anti-inflammatory, immunomodulating, and hepatoprotective, through secondary metabolites of flavonoids, terpenes, and phenolic acids. The Karo people have traditionally used Binara leaves to treat wounds, diarrhoea and heartburn by chewing some of the leaves and then placing them on the wounds outside the body, such as cuts and for diarrhoea and stomach ulcers and placing them around the sick stomach. This study was conducted to know the anti-hyperuricemia effect of the Ethanol Extract of Herba Binara (Artemisia vulgaris L.) on gout rats; phytochemical screening was carried out first to determine the content of Herba Binara (Artemisia vulgaris L.) compounds. The results showed that Herb Binara fulfilled the simplicia characterization requirements and contained secondary metabolites such as alkaloids, flavonoids, tannins, glycosides, saponins and steroids. Herb Binara Ethanol Extract has been shown to reduce uric acid levels in hyperuricemia rats, with the best concentrations being 400 and 800 mg/kg body weight. This was based on significantly different results p>0.05 compared to the positive control group.